Inovação gerencial em um Instituto Nacional de Ciência e Tecnologia (INCT): um modelo para redes de pesquisa formais com perfil empreendedor - Edes Garcia da Costa Filho (2022)
This thesis proposes a reference operational model for formal research networks that aim to interact and collaborate with companies. Supported by a theoretical basis that associate research and innovation networks and the systemic thinking, the model was developed based on a descriptive and qualitative methodological approach, with longitudinal design, through a historical analysis. From a simple sample, the historical analysis involved the investigation of the historical course of almost 8 years of existence of a research network created in 2014 and funded by the National Institutes of Science and Technologies Program (NIST). The collection of documents, direct observation and semi-structured interviews enabled the identification of strategic decisions taken over time in a research network and their unfolding in business processes (activities). Subsequently, activity system maps were developed to relate organizational strategies with the business processes necessary to implement them. Based on the activity system maps, the business processes of the research network were structured and organized in a value chain. The historical analysis highlighted the different business processes institutionalized by a research network along part of its historical course, revealing its mode of operation to interact and collaborate with companies. The results obtained through the historical analysis served as input for the development of a viable system model of the research network, which can serve as an operational reference model for other networks that aim to collaborate with companies. This thesis pointed out how a research network with an entrepreneurial profile interacts and collaborates with companies to promote the innovation process. The historical analysis and the viable system model contribute to the evolution of the research network concept, adding this vision to the existing conceptual debate. It is expected that this model, which can be improved in future studies, serve as a reference and help formal research networks in the institutionalization of business processes and organization of their operation in order to enhance their relationship with companies.